The Tumbang Batu Model of Islamic Eco-Resistance: Interweaving Iḥsān and Indigenous Wisdom Against Extractive Development - Wakhidah, Nur; Alias, Muhammad Nazir; Safii, Safii (Universitas Islam Negeri Raden Fatah Palembang, 2026)
Environmental degradation in Kalimantan is not only an ecological crisis but also a challenge to the ethical foundations of local communities. This study aims to explore how the Muslim community in Tumbang Batu integrates local Dayak-Malay wisdom with the Islamic ethic of iḥsān in formulating resistance to the expansion of the palm oil industry. Using a qualitative approach and social construction theory, data were collected through in-depth interviews, participant observation, and documentation of community practices. The results reveal that forest preservation in Tumbang Batu is understood as